IDENTIFIKASI POTENSI, PENILAIAN KERUSAKAN DAN KERUGIAN LONGSORLAHAN SERTA ARAHAN KONSERVASI LAHAN DI KECAMATAN KARANGGAYAM KABUPATEN KEBUMEN TAHUN 2014 (IMPLEMENTASI UNTUK PENGAYAAN SUPLEMEN BAHAN AJAR PADA KOMPETENSI DASAR MENGANALISIS HUBUNGAN MANUSIA D - Ninayaroh, Dwi (Pendidikan Geografi, 2014)
ABSTRACTDwi Ninayaroh. The Identification of Potency, Landslide Damage and Loss Assessment and Land Conservation Guideline in Karanggayam District Kebumen 2014 (The implementation on the Basic Competence: Analyzing Human Relation with the Environment as a Result of the Lithosphere Dynamics in the topic of the Effect of Exogenous Processes towards Life for High School Students Class X). Thesis. Faculty of Teacher Training and Education Sebelas Maret University Surakarta. August 2014.The purposes of this study were to know: (1) the potency of landslide in Karanggayam District, (2) the level of damage and loss caused by landslide in Karanggayam District, (3) the guideline of land conservation land in the landslide potential area in Karanggayam District, (4) the implementation of study results as teaching materials in schools.This study was conducted under qualitative descriptive survey method with spatial analysis. The population in this study was 146 land units located in Karanggayam District. The technique of sampling was area sampling for each land units, which is 99 land units and purposive sampling was employed for respondents/informants, which is 22 respondents. The technique of data collection used field observation, documentation, interview, and laboratory testing. Data triangulation was used to valid the data (source validation). The technique of data analysis to identify landslide potency using scoring parameters ? landslide parameter determiner which is further was analyzed to determine the landslide damage and loss using P3B guidelines BAPPENAS (2008) modified, so it could be done using the land conservation guideline of the Ministry of Agriculture (2006).The results showed that (1) the landslide potency in Karanggayam District consists of four, namely low landslide potency had 61.89 ha in wide or occupied 0.32% of the total area. For the moderate landslide potency had 2223.43 ha in wide or 11.44% of the total area. For high landslide potency had 15286.61 ha in wide or 78.68% of the total area. For a very high landslide potency had 1857.36 ha in wide or 9.56% of the total area. (2) The result of landslide damage and loss assessment showed that Karanggayam District experienced light damage and did not cause significant losses in the fields, gardens, and dry sector with the kinds of landslide were Rotational Landslide, Topples, Debris Flow, Block Translational Slide, Translational Slide, and Earth Flow. While the settlement and the forest sector has not experienced landslide yet (3) Land conservation guideline was conservation steps which widely use with 12238.62 Ha in wide or 63.14% of the total area (4) The results of the study were implemented as teaching materials in schools. Keywords: Landslide Potency, the Damage and Loss Assessment, Land Conservation Guideline, Geography Learning